ความชุกและปัจจัยทางการยศาสตร์ที่สัมพันธ์กับความผิดปกติของระบบกล้ามเนื้อและกระดูก จากการทำงานในบุคลากรศูนย์จ่ายกลาง โรงพยาบาลระดับตติยภูมิ - หมอนมี จันทร์ธิมาศ (Region 3 Medical and Public Health Journal - วารสารวิชาการแพทย์และสาธารณสุข เขตสุขภาพที่ 3, 2026)
Objective: To investigate the prevalence and factors associated with work-related musculoskeletal disorders (WMSDs) among Central Sterile Supply Department (CSSD) personnel in a tertiary care hospital. Method: A cross-sectional descriptive study was conducted among 40 CSSD workers. Data were collected using a demographic questionnaire, work-related information form, and the Thai version of the Nordic Musculoskeletal Questionnaire. Data analysis employed descriptive statistics and inferential statistics to analyze the relationships of related factors, chi-square test and multiple logistic regression. Results: The 12-month and 7-day prevalence of WMSDs were 67.5% (95% CI: 52.4-82.6) and 50.0% (95% CI: 34.4-65.6), respectively. The most affected areas were the lower back (55.0%), shoulders (45.0%), and hands/wrists (40.0%). Significant predictors included repetitive work (AOR=5.47, 95% CI: 1.03-29.07) and lifting objects >10 kg (AOR=4.85, 95% CI: 1.95-24.76). Conclusions: CSSD personnel showed high prevalence of WMSDs. Repetitive work and heavy lifting were major risk factors. Systematic ergonomic prevention measures should be developed. Keywords: musculoskeletal disorders, central sterile supply department, ergonomics, occupational health.